Determine o valor da expressão abaixo:
x=((-7).4+(-3)/8+-6-(-4))/2
Soluções para a tarefa
Respondido por
1
Ola Elias
x=( (-7)*4 + (-3)/8 -6-(-4) )/2
x = (-28 - 3/8 - 6 + 4 )/2
x = (-30 - 3/8)/2
x = -15 - 3/16
x = (-15*16 - 3)/16 = (-240 - 3)/16 = -243/16
x=( (-7)*4 + (-3)/8 -6-(-4) )/2
x = (-28 - 3/8 - 6 + 4 )/2
x = (-30 - 3/8)/2
x = -15 - 3/16
x = (-15*16 - 3)/16 = (-240 - 3)/16 = -243/16
Perguntas interessantes
Matemática,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás